Characterization of the VVV survey RR lyrae population across the southern galactic plane - Minniti, Dante; Dékány, István (Arxiv, 2017)
Deep near-IR images from the VISTA Variables in the V\'ia L\'actea (VVV) Survey were used to search for RR Lyrae stars in the Southern Galactic plane. A sizable sample of 404 RR Lyrae of type ab stars was identified across a thin slice of the 4$^{\rm th}$ Galactic quadrant ($295\deg < l < 350\deg$, $-2.24\deg < b < -1.05\deg$). The sample's distance distribution exhibits a maximum density that occurs at the bulge tangent point, which implies that this primarily Oosterhoff type I population of RRab stars does not trace the bar delineated by their red clump counterparts. The bulge RR Lyrae population does not extend beyond